(untitled) (Medical Forum Monthly, 2022)
Objective: The purpose of this study is to identify depression among main cares of drug-using patients. Study Design: Descriptive study Place and Duration of Study: This study was conducted at the Sahara Medical College Narowal from October, 2021 to April, 2022. Materials and Methods: In this study, a total of 116 patients of both sexes were presented. The patients ranged in age from 20 to 60 years. After receiving informed written consent, the patient's full details, including age, sex, and body mass index were collected. In the primary caregivers of patients who used psychoactive substances and depression were measured. The SPSS 24.0 version was used to examine all the data. Results: Among 116 caregivers, females were higher in numbers 67 (57.8%) as compared to males 49 (42.2%). Majority of the cases 75 (64.7%) were married and had poor socio-economic status in 86 (74.1%) cases. Most common abusive drug was alcohol, followed by heroin and cannabis. Family history of mental illness found in 20 (17.2%) cases. We found majority of the cases 80 (68.9%) had duration of care >3years. Frequency of depression was found among 83 (71.6%) caregivers in whom most of the cases 52 (62.7%) had severe, followed by moderate depression in 26 (31.3%) cases. Conclusion: We came to the conclusion that caregivers of patients with substance use disorders are more likely to experience depression, and that early treatment is necessary to improve their mental health.